Correlates of Interpersonal Ethnoracial Discrimination Among Latino Adults with Diabetes: Findings from the REACH Detroit Study. Issue 1 (2nd January 2017) - LeBrón, Alana M. W.; Spencer, Michael; Kieffer, Edith; Sinco, Brandy; Piatt, Gretchen; Palmisano, Gloria
ABSTRACT: The purpose of this study is to identify the social and economic correlates of reported experiences of interpersonal ethnoracial discrimination among Latino adults in Detroit. We examine whether the correlates of interpersonal ethnoracial discrimination vary according to the domain of discrimination and compare findings for individual domains of discrimination to a composite measure of experiences of discrimination. This study suggests that the frequency of reported discrimination is moderately high, and relatively common among Latinos with diabetes who live in Detroit. The findings demonstrate that immigration and ethnicity-related factors, such as greater comfort speaking Spanish and being born in the United States, were persistent correlates of more frequent encounters of interpersonal ethnoracial discrimination. Implications for social work research and practice are presented.